(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Health insurance and its benefits are of great importance and impact on the employees who represent the human capital of each organization because they are related to the health reality. The study took into account the most important and the last of his writing of the concepts and literary reviews and enriched the theoretical part of the practical side has addressed the financial data and analysis for the period from 2013 to 2017 to know the impact and the relationship between the variables that They were reviewed on the theoretical side. The study came out with a number of results, on the basis of which practical conclusions were drawn and reflected what was observed on the basis of which the recommendations were formulated